The history of rhythmic gymnastics for women - Sakran Hamza, Jamal; Shhab Ahmed, Zahraa; Abdel Wahed, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The study included three topics and a conclusion; the introduction included the research and its importance, which dealt with the history of the development of women’s sports and the entry of women in many sports after they were not allowed to participate in them. It was its first Olympic participation in the gymnastics game in 1928, and the International Gymnastics Federation divided the gymnastic exercises into seven types. The practice of rhythmic gymnastics is restricted to women only, which is an important movement activity especially for its harmony with the natural biological characteristics of it. Rhythmic gymnastics is performed on a mat similar to that used in artistic gymnastics. Therefore, the importance of the research lies in the researcher’s attempt to study the rhythmic gymnastics in a historical study until it reached the Olympic Games and, accordingly, the role it played in the development of the gymnastics. As for the first topic, it deals with the history of the gymnastics game, which requires a great physical effort and an understanding of why the Greeks use it to develop the body and as a competition in the Olympics. Gymnastics was included in the first Olympic Games in 1896. But they were only men and also took up rhythmic gymnastics, which is one of the most impressive and exciting women’s sports in the world, and the many benefits of teaching rhythmic gymnastics. "Rhythmic gymnastics history is rooted in European traditions; in 1961, modern gymnastics was recognized by the International Gymnastics Federation. The first world championships were held in individual gymnastics in Budapest in 1963. ... In the first Olympic Games, they took place in 1984 in Los Angeles, where Canadian Laurie Fung became the first Olympic champion in modern gymnastics. As for the second topic, it dealt with the rhythmic gymnastics tools, with a historical overview and the material manufactured from them, a description of each instrument, a description of exercises with their difficulty, and the use of music with the kinematic chain and performance time. The third topic dealt with the Olympic Games and its years of hosting them in the countries hosting them and the individual and team results of the players and the participating countries with tables showing the individual and different results. As for the conclusion, it deals with the evolution of the rhythmic gymnastics game, the association of this type with women only, the development of tools during time and its attainment of what it is today, the Olympic competitions and the Russian players’ excellence in it because of their physical strength, high flexibility and accuracy in performance